A woman complicated by sudden cardiac arrest owing to spontaneous coronary artery dissection after stillbirth. Issue 2 (February 2021) - Numasawa, Yohei; Yokokura, Souichi; Maeda, Takashi; Daigo, Kyohei; Sakata, Shingo; Hashimoto, Ryota; Taruoka, Akira; Sato, Kazuki; Haginiwa, Sho; Kojima, Hidenori; Tanaka, Makoto
Abstract: Spontaneous coronary artery dissection (SCAD) is the most important cause of acute coronary syndrome in pregnant women. Pregnancy-associated SCAD frequently occurs in the third trimester or postpartum period. However, little is known regarding the relationship between the occurrence of SCAD and stillbirth. We describe here a 41-year-old woman complicated by sudden cardiac arrest owing to SCAD in the distal segment of the right coronary artery 13 days after stillbirth. After contacting emergency medical services, she was resuscitated by an automated external defibrillator because the initial electrocardiographic waveform was ventricular fibrillation. After cardiopulmonary resuscitation, the diagnosis of SCAD was confirmed by coronary angiography and intracoronary imaging, including intravascular ultrasound and optical coherence tomography. The patient was managed with conservative medical therapy because the culprit lesion was present in the distal segment of the right coronary artery and coronary blood flow was preserved. No major adverse cardiovascular events, including recurrent ventricular arrhythmia, were observed during hospitalization. Our findings indicate that pregnancy-associated SCAD leading to sudden cardiac arrest may occur in the postpartum period, even after stillbirth. Intravascular imaging plays a pivotal role in diagnosing SCAD. <Learning objective: Pregnancy-associated spontaneous coronary artery dissection (SCAD) is a relatively rare but well-known cause of acute coronary syndrome in pregnant or postpartum women. However, whether the risk of pregnancy-associated SCAD in the postpartum period is different between normal birth and stillbirth remains unknown. Pregnancy-associated SCAD leading to sudden cardiac arrest owing to acute myocardial ischemia may occur in postpartum women, regardless of fetal survival.>